Iowa Birdline update, March 27, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for March 27, 1989. Highlights include migration reaching full swing for waterfowl and early passerines and the sighting of a mostly white American Robin. Epson - sheet feed/flatbed